Cyclical Implications of Changing Bank Capital Requirements in a Macroeconomic Framework - Ganapolsky, Eduardo (IMF Working Papers; Working Paper ;, 2005)
There is a widespread view that bank capital requirements should be loosened during recessions and tightened during expansions to avoid excessive credit and output swings. This view is based on a partial analysis that ignores the effects of capital requirement policies on the saving decisions of households, and, through this channel, on bank loans and output. We present an intertemporal general equilibrium framework that accounts for such effects and evaluate the optimal responses to loan supply and productivity (loan demand) shocks. In contrast to the standard view, we show that, when loan supply is reduced, increasing the capital requirement allows a faster recovery of households' savings, loans, and output than a flat capital requirement policy. When productivity (loan demand) is reduced, lowering the capital requirement facilitates households' dissaving and amplifies the output decline, but enhances welfare. Finally, we show that if productivity reductions are anticipated-rather than unanticipated-by regulators, lowering the capital requirement preemptively enhances welfare through greater intertemporal smoothing of households' consumption and deposit holdings.